1984
DOI: 10.2170/jjphysiol.34.255
|View full text |Cite
|
Sign up to set email alerts
|

Discharge patterns of the slowly adapting mechanoreceptor afferent units innervating the non-warty skin of the frog.

Abstract: Discharge patterns of slowly adapting (SA) mechanoreceptor afferent units innervating the non-warty skin of frogs, were analyzed statistically. Because SA units in the frog did not always produce sustained discharges for a long period, analysis was carried out on ensembles of interspike intervals (ISIs) obtained in two ways : (1) a series of successive ISIs obtained in the quasi-stationary state of maintained discharges and (2) an ensemble of ISIs (X(1), X(2), .. X(50)), obtained on repeated trials of stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…Ft II units are found only in the non-warty skin, but three other types of mechanoreceptive units are present both in the warty and non-warty skin (OGAWA et al, 1984). In the present study, however, we isolated three of the four types of units only from the warty skin.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Ft II units are found only in the non-warty skin, but three other types of mechanoreceptive units are present both in the warty and non-warty skin (OGAWA et al, 1984). In the present study, however, we isolated three of the four types of units only from the warty skin.…”
Section: Discussionmentioning
confidence: 60%
“…RA type I and RA type II units in both warty and non-warty skin, and two types of SA units, i.e. frog type I (Ft I) units in warty and non-warty skin and frog type II (Ft II) units in non-warty skin (OGAWA et al, 1981(OGAWA et al, , 1984OGAWA and YAMASHITA, 1982). The purpose of the present study was, therefore, to obtain evidence indicating that different types of cutaneous mechanoreceptor afferent units of frogs encode different aspects of mechanical stimulus.…”
mentioning
confidence: 99%
“…The stimulus‐adaptation properties of mechanoreceptors have been classified into two categories: slowly adapting and rapidly adapting receptors ( Iggo, 1976 ) . Ogawa and Yamashita (1982) and Ogawa et al (1984 ) have demonstrated that, in the frog, two types of slowly adapting cutaneous mechanoreceptor afferent units are identified by their firing behavior: irregularly discharging frog type I units responding to mechanical stimulation in both warty and non‐warty skins and regularly discharging frog type II units responding to mechanical stimulation in non‐warty skin. Ogawa (1996 ) suggested that frog type I units consist of an MC–N complex and that Merkel cells function as receptive cells.…”
Section: Discussionmentioning
confidence: 99%